Characterization of bismuth vanadate (BiVO4) nanoparticle prepared by solvothermal method. Issue 175 (12th October 2016) - Longchin, P.; Pookmanee, P.; Satienperakul, S.; Sangsrichan, S.; Puntharod, R.; Kruefu, V.; Kangwansupamonkon, W.; Phanichphant, S.
ABSTRACT: Bismuth vanadate (BiVO4 ) nanoparticle was prepared by solvothermal method. The starting precursors were used as bismuth nitrate pentahydrate (Bi(NO3 )3 5H2 O), ammonium metavanadate (NH4 VO3 ) and absolute ethanol (C2 H5 OH). Solution I: Bi(NO3 )3 5H2 O was dissolved in 2.0 M nitric acid (HNO3 ) and absolute ethanol (C2 H5 OH). Solution II: NH4 VO3 was dissolved in 2.0 M ammonium hydroxide (NH4 OH) and absolute ethanol (C2 H5 OH). The mixed solutions were stirred for 5 min and left into Teflon-lined stainless steel autoclave treatment at 200°C for 3 and 5 h. The yellow final solution was filtered and dried at 100°C for 24 h. All BiVO4 nanoparticle samples were characterized by X-ray diffractometer (XRD), field emission scanning electron microscope (FESEM), energy dispersive X-ray spectrometer (EDXS) and Fourier transform infrared spectrometer (FTIR).